1983
DOI: 10.2527/jas1983.5761463x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus in Swine. VI. Utilization of Nitrogen, Calcium and Phosphorus and Reproductive Performance of Gravid Gilts Fed Two Dietary Phosphorus Levels for Five Parities

Abstract: Sixty-two gilts were paired at breeding and assigned randomly to one of the following dietary treatments: (1) low P or (2) high P during gestation and lactation. Two sets of diets (A and B) were formulated; each set to provide a low (10 g) and high (15 g) daily P intake (equal Ca daily intake, 15 g) when fed at 1.82 and 2.27 kg daily, respectively for sets A and B. Females were fed 1.82 kg daily of set A diets during the first 11 wk of gestation, 2.27 kg daily of set B diets for the next 3 wk and 3.34 kg of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
(41 reference statements)
5
8
0
Order By: Relevance
“…The lack of difference on average weight gain of litters and sow milk production between the different levels and sources of Ca is in agreement with the findings of Komegay and Kite and Kornegay et al who evaluated the use of different Ca and P levels for sows and found no differences on litter size, birth weight nor weaning weight [20,21]. Similarly, Maxon and Mahan, studying first and second parity sows for two consecutive reproductive cycles using a Ca to P ratio of 1.3:1, also found no difference in litter parameters [22].…”
Section: Discussionsupporting
confidence: 80%
“…The lack of difference on average weight gain of litters and sow milk production between the different levels and sources of Ca is in agreement with the findings of Komegay and Kite and Kornegay et al who evaluated the use of different Ca and P levels for sows and found no differences on litter size, birth weight nor weaning weight [20,21]. Similarly, Maxon and Mahan, studying first and second parity sows for two consecutive reproductive cycles using a Ca to P ratio of 1.3:1, also found no difference in litter parameters [22].…”
Section: Discussionsupporting
confidence: 80%
“…absorption of both Ca and P during the gestation period with higher Ca-P intake was in agreement with the findings of Nimmo et al (1981) and Kornegay and Kite (1983). An overall increase in the absorption of Ca and P during both gestation and lactation from the finishing period could be due to an increased metabolic need of these minerals during these periods.…”
supporting
confidence: 90%
“…Measures of skeletal strength or bone mineralization are maximized with increasing dietary Ca:P levels for swine from 5 to 110 kg body weight, 3 weeks to 7 months age, (Chapman et al, 1962;Miller et al, 1962;Libal et al, 1969;Fammatre et al, 1977;Mahan et al, 1980;Nlmmo et al, 1981;Mahan, 1982;Maxson and Mahan, 1983)* Peak adult bone mass does not appear necessary for market swine slaughtered between these ages or weights (Miller and Kornegay, 1983)* Peak adult bone mass developed In market swine and selected to remain in the reproducing herd beyond 110 kg body weight or 7 months of age, 13 controversial (Miller and Kornegay, 1983). Several researchers suggest that structural unsoundness or fractures are unrelated to dietary Ca:P levels during growth above HRC (1979) recommended levels (Nlmmo et al, 1980;Kornegay and Thomas, 1981;Arthur et al, 1983;Kornegay and Kite, 1983)* Conversely, other workers (Kornegay et al, 1973;Thomas and Kornegay, 1981;Nlmmo et al, 1981a;Cromwell, 1982;Mahan and Fetter, 1982) lndioate that pigs may benefit from Increased dietary Ca:P above NRC (1979) recommended levels during growth and as an adult in the reproducing herd. Confounded in these results are sex, age, reproductive status as well as feeding practices, differences in experimental conditions and the criteria used to assess results.…”
Section: Terminologymentioning
confidence: 99%
“…Average weaning weight or the number of pigs weaned has been generally reported unaffected by increasing dietary Ca:P in sows from one to five reproductive cycles (Kornegay et al, 1973;Nimmo et al, 1981a, Hahan andFetter, 1982;Kornegay and Kite, 1983). Therefore, dietary levels of Ca:P, unless they are severely deficient, appear to have little affect on milk production in swine.…”
Section: Structural Soundness Problems (Lameness) Although Lameness Ismentioning
confidence: 99%
See 1 more Smart Citation